Komunikasi Stakeholder pada Program Corporate Social Responsibility PT Semen Gresik dalam Mencapai Social License to Operate - Dwi Prasetyo Wijanarko; Andre Noevi Rahmanto (Universitas Sebelas Maret (UNS), 2026)
The implementation of Corporate social responsibility (CSR) is one of the company's strategies in building legitimacy or social acceptance, also known as social license to operate, as well as strengthening relationships with the community. In the context of PT Semen Gresik, the existence of factory and mining activities directly affects the environment and landscape, and has the potential to cause negative externalities and social problems in the community. Relationships with stakeholders are key to the success of the CSR program at PT Semen Gresik. This is because since the factory was first established, there has been conflict and resistance from some members of the community. Therefore, relationships and communication with the community as the main stakeholders in the CSR program are crucial. This study aims to describe stakeholder communication in CSR programs in an effort to achieve social license to operate. This study uses a descriptive qualitative approach with a case study research method. The theory referred to is the CSR Communication Model by Morsing & Schultz (2006). Data were obtained through interviews, documentation, and observation. The results of the study show that PT Semen Gresik implements stakeholder communication in accordance with the CSR Communication Model. PT Semen Gresik maps community stakeholders and then adjusts them to the appropriate communication strategies so that the communication process can run effectively. This study confirms that the success of stakeholder communication in CSR programs lies in the extent to which companies are able to be open in conveying information, listening to aspirations, and actively involving the role of community stakeholders in every stage of the program.